Factores metereológicos, geofísicos y químicos que influyen en el proceso de erosión de las superficies arquitectónicas de tierra: caso huaca de la luna, valle moche, Trujillo - Morales Gamarra, Ricardo Enrique (2011)
Results of a research about the pathology and degradation on an earthen archaeological monument in the North Coast of Peru are presented, taking as case of study Huaca de la Luna, Moche Valley, as it is a macroregional diagnostic structure due to its geotopographical location, constructive techniques and the impact of meteorological, geophysical and chemical factors. This nationwide pioneering research developed several data obtaining techniques and methods of analysis, organized in relation to the nature of the impact factors and the 11 monitoring and registering stations established en the area of study. The study took as referents the North Facade (Sector A) and South Facade (Sector B) of Huaca de la Luna, to obtain and establish a contrasting line, between a protected sector (North Facade) and others exposed to the direct impact of abrasive winds (South Facade), to determine the different magnitudes of decay. This area were monitored and evaluated each fifteen days, taking in consideration the fixed meteorological station data and the portable equipment in Huaca de la Luna. The implementation of a wind tunnel in lab an the filed has made easier the evaluation of the simulated erosive process. It has been demostrated that the monuments are filed laboratories that make easier the characterization of the architectural pathologies, generating a research process for the conservation and development of trusworthy experiments about the structural stabilization and enviromental conditions. Research has demostrated that earthen archaeological structures are mainly affected by winds and higrothermic changes, determining a framework of fragility, fatigue and extreme vulnerability, that generate a loss of mass in relation to the technique and constructive materials, exposition conditions, wind speed and windblown materials.